In silico Rational Designing, Synthesis, Characterization, and Biological Evaluation of Novel Pyrazole Derivatives as Potential Anti-Cancer and Anti-Microbial Agents - Narwal, Sangeeta; Dhanda , Tilak; Devi, Bhagwati (Journal of Neonatal Surgery, 2025)
Pyrazole derivatives have garnered significant attention in medicinal chemistry due to their diverse pharmacological activities, including anti-cancer and anti-microbial properties. This study focuses on the in silico rational design, synthesis, and characterization of a series of novel pyrazole-based compounds aimed at addressing microbial resistance and cancer proliferation. Using Schrödinger software suite, molecular docking against matrix metalloproteinase-9 (MMP-9, PDB ID: 6ESM) identified promising leads with binding energies ranging from -7.2 to -9.1 kcal/mol. Fifteen pyrazole derivatives were synthesized via multi-component reactions, achieving yields of 65-92%. Characterization via FTIR, 1H-NMR, 13C-NMR, and HRMS confirmed structural integrity. In vitro anti-microbial assays against Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria, as well as fungi (Candida albicans), revealed MIC values as low as 3.12 µg/mL for compound 6. Anti-cancer evaluation on MCF-7 (breast) and HCT-116 (colon) cell lines showed IC50 values of 4.5-12.3 µM, with compound 6 exhibiting superior potency. Pharmacokinetic predictions indicated favorable drug-likeness (Lipinski's rule compliance) and bioavailability scores >0.55. These findings underscore the potential of these pyrazoles as dual-action therapeutic agents, warranting further in vivo studies